Upaya Meningkatkan Hasil Belajar Ekonomi Melalui Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) pada SMA Negeri 4 Palangka Raya: Efforts to Improve Economic Learning Outcomes Through Cooperative Learning Type Numbered Head Together (NHT) at Palangka Raya 4 High School - Hariyanto, Minggus; Suyati, Endang Sri (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to find out the learning activities and increase the learning outcomes of students in class XI-8 on Economic subjects using the NHT type cooperative learning model. The method used in this study is Classroom Action Research (CAR). The items in this study were all students of class XI-8, amounting to 37 people at SMAN 4 Palangka Raya. Data collection techniques needed in this study are Observation, Documentation and Test. The data analysis technique used is qualitative and quantitative. The results of the study concluded that Learning activities of students became more active. This is evidenced by the response of students to a more vibrant learning process so that it can be said that the Numbered Head Together (NHT) learning model is useful for improving economic learning outcomes, (2) There is an increase in learning outcomes. The average test results obtained by students in the first cycle 59 with the percentage of classical 35% and the second cycle obtained an average of 88 with a rate of 90% classics.